MAGYAR ÖNKORMÁNYZATI TULAJDONÚ TÁRSASÁGOK PÉNZÜGYI TERVEZÉSI MÓDSZEREI - Menich-Jónás, Judit; Kovács-Rump, Henetta (Acta Carolus Robertus, 2021)
Local governments set up companies to carry out certain of their public tasks defined by law. To do this, they have to provide their companies with property that they must manage responsibly. Therefore, the management and financial stability of both the local government and the municipal company affect the operation of the other organization. The current legislation does not clearly define when a company is considered as municipally owned. Although planning is an essential part of efficient and stable operation, in Hungary, planning is not required by law for these companies. But they usually prepare an annual business plan, which is approved by the owner. In our research, we examined whether companies can use the budget planning methods of the owner municipality. Generally speaking, these companies do not plan in a uniform structure, as there are no regulations for the formal and content elements of their business plan. The financial plans are not standardised and do not provide a financial presentation of the implementation of the previous year’s plan, thus comparisons cannot be made. The main difficulties in planning are the lack of managerial accounting and sufficient and adequate human resources. The Covid-19 pandemic has also made planning for these companies more difficult, as in 2020 it was not yet possible to foresee how much the pandemic would affect the operations and financing of each company.